Types of Nostalgia in Bader AL- Shaker AL-Sayyab Poetry - Reza Mirahmadi; Ali Najafi Ivaki; Najmah Fathalizadfh (دراسات في اللغة العربيّة وآدابها)
Nostalgia is a term frequently used in recent years by poetry critics. Though recently gaining momentum in Arabic criticism, it had existed since per-Islamic era and is motivated by personal, political, social, and emotional factors. A poet living in exile or suffering from the socio-political situation may resort to nostalgia. Taking the above-mentioned factors into consideration, we can categorize this technique into personal and social types. At present, nostalgia originates in political, social, and personal concerns and AL-Siab, the pioneer of blank poetry, is a one of the most popular poets whose poems reflect his desire and enthusiasm for his childhood, country and homeland. The findings of the present research indicate that Badr Al-Shaker often took refuge in his happy, cheerful past to forget the sorrows engulfing his life. This article studies nostalgia ,types, and reasons in Al-Siabs poetry.